PICTIONARY GAME FOR VOCABULARY MASTERY: BEST PRACTICE FROM A RURAL SCHOOL CONTEXT - Odang, Aurelia Stefania; Uran, Stefanus Igolois Grenga; Janggo, Wendelinus Oscar (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
While online gamification in education settings has spread worldwide in this digital era, its application gets confronted with massive opposition, especially in rural contexts. Several technologically inaccessible schools may find it unfavourable to apply such a model in learning. This study looks at redefining a simple application of particular Pictionary games to boost students’ English vocabulary learning in a predominantly rural, private school setting. It aims at improving students’ vocabulary mastery through the plain-sailing Pictionary game technique and re-establishing the teacher’s best practices to apply. Two-cycle classroom action research was applied by collecting data through observation, questionnaires, interviews, and tests. The qualitative data analysis shows better-changing activities, attitudes, perceptions, and learning experiences leading to the positive outcomes of the game application. Quantitative data on students’ vocabulary tests in two-prioritized skills (reading and listening) also show a remarkable improvement from cycle one to cycle two, with the class percentage passing the success criterion for reading and listening vocabulary mastery being 83.33% and 75%, respectively. In addition, the teacher’s reflection on each cycle shapes profound insights into several contextual best practices: goal-oriented teaching, progressiveness, shift gears, differentiated learning, pace and variety, and encouragement.